A novel approach to create an antibacterial surface using titanium dioxide and a combination of dip-pen nanolithography and soft lithography (2018)
Soft lithography and Dip-Pen Nanolithography (DPN) are techniques that have been used to modify the surface of biomaterials. Modifed surfaces play a role in reducing bacterial adhesion and bioflm formation. Also, titanium dioxide has been reported as an antibacterial substance due to its photocatalytic efect. This work aimed at creating patterns on model surfaces using DPN and soft lithography combined with titanium dioxide to create functional antibacterial micropatterned surfaces, which were tested against Streptococcus mutans. DPN was used to create a master pattern onto a model surface and microstamping was performed to duplicate and transfer such patterns to medical-grade stainless steel 316L using a suspension of TiO2. Modifed SS316L plates were subjected to UVA black light as photocatalytic activator. Patterns were characterized by atomic force microscopy and biologically evaluated using S. mutans. A signifcant reduction of up to 60% in bacterial adhesion to TiO2-coated and -micropatterned surfaces was observed. Moreover, both TiO2 surfaces reduced the viability of adhered bacteria after UV exposure. TiO2 micropatterned demonstrated a synergic efect between physical and chemical modifcation against S. mutans. This dual efect was enhanced by increasing TiO2 concentration. This novel approach may be a promising alternative to reduce bacterial adhesion to surfaces.